Rufus Wainwright [entrevista]: Geni i figura - Broc, David (Benzina: Revista d'excepcions culturals, 2007)

Rufus Wainwright. Interview by Paul Zollo - Zollo, Paul (Song: the World’s Best Songwriters on Creating the Music that Moves Us, 2007)
Song is an enthralling compilation of songwriting wisdom from 100 of the biggest names in music. From country to rock to folk to alternative, this genre-spanning collection of interviews captures the anecdotes, history, and wisdom of the best songwriters around - in their words. An entertaining read as well as an indispensable guide to the art and craft of songwriting, Song is a must-have resource for the aspiring, amateur, or professional musician. Inside, you'll find entertaining and enlightening interviews from great songwriters such as Smokey Robinson, Willie Nelson, Jewel, Kenny Chesney, Cat Stevens, Jack Johnson, Sheryl Crow, John Legend, John Mellencamp, Ray Charles, Clint Black, Rob Thomas, Dolly Parton, Rufus Wainwright, Bob McDill, Lyle Lovett, Keith Urban, Beck, M. Ward, Lou Reed, Roger Miller, Grant-Lee Phillips, and John Denver.